Regulatory and Economic Foundations for Integrating EU Environmental Standards in Architectural and Construction Enterprises - Kubanov, Ruslan; Denysiuk, Olga; Makatora, Dmytro (Odessa Polytechnic National University, 2026)
The article examines the regulatory, legal and economic foundations for integrating European Union environmental standards into the activities of Ukrainian architectural and construction enterprises. The relevance of the topic is determined by the need to harmonize national legislation with European directives and regulations, as well as by the necessity to enhance the competitiveness of the sector in the context of sustainable development and climate challenges. Key barriers to implementation have been identified, including legal uncertainty, high costs, insufficient staff awareness, and weak institutional support. The main areas of integration are analysed, such as green construction, circular economy policies, the interaction between environmental and climate strategies, and the CEN/TC 350 standards. The methodology combines systemic, legal, economic, and comparative approaches, using case studies and LCA/LCC methods. A roadmap for the implementation of standards is proposed, covering audit, planning, training, modernization, reporting, and monitoring. The results confirm that the integration of EU environmental standards serves as a source of economic efficiency, investment attractiveness, and a positive corporate image, forming the basis for a sustainable development strategy of Ukraine’s construction industry.
Нормативно-правові та економічні засади інтеграції екологічних стандартів ЄС у діяльністьархітектурно бідівельних підприємств
Keywords: EU environmental standards; regulatory and legal framework; architectural and construction enterprises; economic mechanisms; green construction; circular economy; environmental management; legislative harmonization; економічні механізми; «зелене» будівництво; циркулярна економіка; екологічний менеджмент; гармонізація законодавстваекологічні стандарти ЄС; архітектурно будівельні підприємства; нормативно правове регулювання; 349.6:658.26:330.15:69(477)(4ЄС)